2007
DOI: 10.1016/j.bbamem.2007.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Structure analysis of the protein translocating channel TatA in membranes using a multi-construct approach

Abstract: The twin-arginine-translocase (Tat) can transport proteins in their folded state across bacterial or thylakoid membranes. In Bacillus subtilis the Tat-machinery consists of only two integral (inner) membrane proteins, TatA and TatC. Multiple copies of TatA are supposed to form the transmembrane channel, but little structural data is available on this 70-residue component. We used a multi-construct approach for expressing several characteristic fragments of TatA(d), to determine their individual structures and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…The low transport activity of our TatA-YFP fusion is consistent with other studies that used fusions to the C terminus of TatA (refs 38 and 39 and T.P., unpublished observations) and occurs even though the last Ϸ50 aa of TatA have a random coil structure (12,40). Steric hindrance to the movement of the substrate is a likely explanation for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
“…The low transport activity of our TatA-YFP fusion is consistent with other studies that used fusions to the C terminus of TatA (refs 38 and 39 and T.P., unpublished observations) and occurs even though the last Ϸ50 aa of TatA have a random coil structure (12,40). Steric hindrance to the movement of the substrate is a likely explanation for this phenomenon.…”
Section: Discussionsupporting
confidence: 90%
“…1C and Refs. [55][56][57][58]. Furthermore, functional analyses suggested that the conserved hinge region connecting both helices might be of structural importance for TatAd (50).…”
Section: Discussionmentioning
confidence: 99%
“…However, currently no detailed structures of the TAT apparatus or of any of its individual proteins (i.e., TatA, -B, or -C) currently exist for molecular modeling with promising lead compounds (32,43,67). Additionally, although an in vitro based assay of TAT function has been described for E. coli TAT, it has not yet been used for evaluating small-molecule TAT inhibitors, and it has not yet been developed for the P. aeruginosa TAT system (70).…”
mentioning
confidence: 99%